Pemimpin: Sebuah Komposisi Karawitan - BAMBANG SRI ATMOJO (Institut Seni Indonesia Yogyakarta, 2008)
The Leaders. This karawitan compotition based on the current situations of Indonesian political leaders andgovernment. As we can see from printed and electronic media, there are political leaders and government peoplewho corrupt, violate the laws, and so on. This has inspired the writer to write a piece of karawitan compositionentitled “The Leader”. In this composition, the writer is trying to criticize the situations, give some moral messages,and ask people not to follow the bad examples of those leaders. The process of composition has involved phaseslike exploration of the ideas, improvisation, and composition. This composition is played softly in laras pelog patetbarang and it can take the form of ladrang, ayak-ayak, lancaran and playon.